Working-class girls' construction of learner identities and aspirations through engagement in Chinese language education in Australia. Issue 6 (2nd November 2022) - Xu, Wen; Stahl, Garth
ABSTRACT: Despite suspicions concerning the global expansion of Chinese as a Foreign Language (CFL) education, the teaching of Chinese is often a mainstay within global citizenship and elite education. With this paradox in mind, the paper draws on theories of classed selfhood and learner identities to explore the possibilities of CFL to influence the learner identities of five working-class girls. Through drawing on their narratives, we glimpse the ways in which the pedagogic practices of CFL inform their understandings of their education and future – specifically their academic aspirations, career choices, and dreams of wealth. Considering the role of CFL in their lives requires a criticality regarding the neoliberal agenda shaping the educational experiences of young women as well as how they construct their subjectivities in relation to what makes a 'good' student and an 'ideal' citizen.